2015
DOI: 10.1002/admi.201500445
|View full text |Cite
|
Sign up to set email alerts
|

Roll‐to‐Roll Production of Graphene Hybrid Electrodes for High‐Efficiency, Flexible Organic Photoelectronics

Abstract: transparent conductive electrode and substrate material is the combination of indium tin oxide (ITO) and glass with a share of over 95% throughout the scientifi c community. [ 2 ] Future commercial electronic devices require versatile features, such as fl exibility, being lightweight and low cost, wearability, and a superior mechanical stability. [ 3,4 ] In addition, the fabrication of such devices is based on solution processing methods known as "printable electronics," which ultimately integrate multidimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…The X‐ray diffraction (XRD) patterns of PEDOT:PSS and PEDOT:PSS/HI films are revealed in Figure b. The peaks of 2θ at 3.8° and 23–26° are main characteristic peaks for carbon materials (PEDOT and GO) . It is an evident change in d (100) peak of the FTEs with and without HI treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The X‐ray diffraction (XRD) patterns of PEDOT:PSS and PEDOT:PSS/HI films are revealed in Figure b. The peaks of 2θ at 3.8° and 23–26° are main characteristic peaks for carbon materials (PEDOT and GO) . It is an evident change in d (100) peak of the FTEs with and without HI treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It requires that FTEs have versatile features, such as superior optoelectronic properties, lightweight portability, low cost, and mechanical flexibility . In addition, preparation of FTEs is based on printable methods, which can be ultimately integrated in roll‐to‐roll processing . The indium tin oxide is the prototypical material for FTEs, but film fragility, high cost (materials and fabricating process), and dissatisfactory optoelectronic property are inevitable barriers for certain commercial applications …”
Section: Introductionmentioning
confidence: 99%
“…Roller‐associated technology is one of the technologies satisfying the demand of high‐throughput production, such as roller imprinting of large‐area micro/nanostructures and roll‐to‐roll production of electronic devices, and has been widely explored from laboratory to industrial production. Here, inspired by this technique, we developed an innovative roller‐assisted adhesion imprinting (RAI) toward high‐throughput and large‐area manufacturing of SOLEDs with ordered wrinkles.…”
mentioning
confidence: 99%
“…Among these various stretching strategies, ordered wrinkles-based SOLEDs are able to satisfy these requirements by exhibiting 100% strechability, high efficiency of 70 cd A −1 , and cyclic stretching stability of withstanding 20 000 stretch-release cycles, respectively. [1,19] However, highthroughput, large-area, and cost-efficient manufacturing of the ordered wrinkles-based SOLEDs is still a challenge.Roller-associated technology is one of the technologies satisfying the demand of high-throughput production, such as roller imprinting of large-area micro/nanostructures [21][22][23][24] and roll-to-roll production of electronic devices, [25][26][27][28][29] and has been widely explored from laboratory to industrial production. Here, inspired by this technique, we developed an innovative rollerassisted adhesion imprinting (RAI) toward high-throughput and large-area manufacturing of SOLEDs with ordered wrinkles.…”
mentioning
confidence: 99%
“…To find the figure of merit at 90% transmissivity (ϕTC), the equations can be adjusted to Equation With this equation, again the higher numbers indicate higher performance. In that same study FOM values were reported for rGO films reported in the range of .189 to 0.232, 21 70.0 for Ag NWs, and 134.4 to 189.9 for their hybrid Ag NW/rGO films (whereas a typical FOM value for ITO would be 297). 17 FOMs of the aforementioned TCFs in Table 1 have been calculated and are displayed in Figure 10.…”
Section: Conductive Precursorsmentioning
confidence: 65%